Analisis Reaktivitas Thorium Molten Salt Reactor 500 Berdasarkan Skenario Penggunaan Control Rod Menggunakan OpenMC - Eza Pelita Zebua, Fajri; Handayani Irka, Feriska; Raflis, Helen; Fardela, Ramacos; Fitriyani, Dian (Jurnal Fisika Unand, 2025)
Neutron calculation simulation with the TMSR-500 conceptual reactor model was carried out for the development of reactivity control in the reactor. The control of reactivity is regulated by the use of a control rod for the shutdown rod and a regulating rod on the reactor. The simulation was carried out using OpenMC computational code and the nuclear data ENDF/B-VII.1. The reactivity value is calculated based on the use scenario of the control rod for each reactor operating condition set with a reactivity margin limit of ≤ 5% dk/k to control reactivity during operation and ≤ 0,5% dk/k during shutdown. The simulation of reactivity control during operation was calculated based on the use scenario of 0% Gd2O3-100% graphite, 25% Gd2O3-75% graphite, 50% Gd2O3-50% graphite, 75% Gd2O3-25% graphite, and 100% Gd2O3-0% graphite. Then, in the shutdown condition, the scenario is set with the use of control rods by Gd2O3 and graphite. The simulation results show that the reactor has an excess reactivity of >5% dk/k. The Control Safety Device (CSD) simulation is able to suppress reactivity ≤ 5% dk/k, but the flux distribution is unevenly distributed. The results of the calculation on the optimization the reactor by the fuel radius with the scenario of using a control rod of 25% graphite-75% Gd2O3 succeeded in controlling the reactivity with a margin of 1,0111±0,00013 (0,108% dk/k). Based on the research, the criticality level of the TMSR 500 is determined by the optimization of the fuel radius and the reactivity can be controlled based on the use scenario of the control rod.